Extraneural Supratentorial Primitive Neuroectodermal Tumor Metastasis: An Adult Case Report - Nidhal Matar; Kamel Bahri; Jallel Kallel; Adnene Boubaker; Hafedh Jemel (Indian Journal of Neurosurgery)
Extraneural metastases of supratentorial primitive neuroectodermal tumors (PNET) are very rare and have been reported in only sporadic cases. We present a patient with supratentorial PNET metastasizing to the lung, diagnosed 4 months after cerebral surgery.